Teachers' Opinions On Unethical Pro-Organizational Behaviors Encountered In Schools - Demirkol, Murat; Özan, Mukadder Boydak; Karagözoğlu, Ahmet Alper (Salim DURUKOĞLU, 2024)
The aim of this research is to examine the views of teachers working in public schools about the unethical behaviors of school principals for the benefit of the organization. This study was designed in the phenomenology pattern, which is one of the qualitative research methods. The research was carried out voluntarily with 38 teachers who received a non-thesis master's degree in the field of Educational Administration at the Fırat University Institute of Educational Sciences in the 2022-2023 academic year. In the research, a semi-structured interview form was developed in order to determine the opinions of the teachers and the descriptive analysis method was used. Within the framework of the opinions received from the teachers, the unethical behaviors of the school principals for the benefit of the organization; It was found that it was done in order to provide financial resources to the institution, to protect the image of the institution, and to prevent the pressure of politicians and stakeholders. It is seen that the participants are sensitive about ethical principles. The unethical behaviors of the school principal for the benefit of the organization, the organization; It is stated that it may disrupt its functioning, damage its culture and image, and cause loss of reputation. Another finding obtained in the research is that the participants; It shows that they have the perception that unethical behaviors for the benefit of the organization will cause great harm to the organization and that they may face legal problems.

Bu araştırmanın amacı resmî okullarda görev yapan öğretmenlerin, okul müdürlerinin örgüt yararına sergiledikleri etik dışı davranışlara ilişkin görüşlerini incelemektir. Bu çalışma nitel araştırma yöntemlerinden olgu bilim (fenomenoloji) deseninde tasarlanmıştır. Araştırma 2022-2023 eğitim öğretim yılında Fırat Üniversitesi Eğitim Bilimleri Enstitüsü Eğitim Yönetimi alanında tezsiz yüksek lisans eğitimi gören 38 öğretmen ile gönüllü olarak yürütülmüştür. Araştırmada öğretmenlerin görüşlerini belirleyebilmek amacı ile yarı yapılandırılmış görüşme formu geliştirilmiş ve betimsel analiz yöntemi kullanılmıştır. Öğretmenlerden alınan görüşler çerçevesinde, okul müdürlerinin örgüt yararına sergilediği etik dışı davranışların; kuruma maddi kaynak sağlamak, kurum imajını korumak, siyasilerin ve paydaşların baskısını önlemek amacıyla yapıldığı bulgusuna ulaşılmıştır. Katılımcıların etik ilkeler konusunda hassas olduğu görülmektedir. Okul müdürünün örgüt yararına sergilediği etik dışı davranışların, örgütün; işleyişini bozabileceği, kültürüne ve imajına zarar vereceği, itibar yitimine uğrayacağı ifade edilmektedir. Araştırmada elde edilen başka bir bulgu; katılımcıların, örgüt yararına etik olmayan davranışların örgüte büyük zarar vereceği ve hukuki sorunlarla karşı karşıya kalınabileceği algısına sahip olduklarını göstermektedir.
Okullarda Karşılaşılan Örgüt Yanlısı Etik Olmayan Davranışlar Hakkında Öğretmen Görüşleri
Keywords: Educational Administration; Supervision; Planning and Economics (Other); Eğitim Yönetimi; Teftişi; Planlaması ve Ekonomisi (Diğer)